Rhodium-Catalyzed Addition of Organozinc Iodides to Carbon-11 Isocyanates - Mair, Braeden A; Fouad, Moustafa H; Ismailani, Uzair S; Munch, Maxime; Rotstein, Benjamin H (Université d'Ottawa | University of Ottawa, 2020)
Amides were prepared using rhodium-catalyzed coupling of organozinc iodides and carbon-11 (11C, t1/2 = 20.4 min) isocyanates. Nonradioactive isocyanates and sp3 or sp2 organozinc iodides generated amides in yields of 13%-87%. Incorporation of cyclotron-produced [11C]CO2 into 11C-amide products proceeded in yields of 5%-99%. The synthetic utility of the methodology was demonstrated through the isolation of [11C]N-(4-fluorophenyl)-4-methoxybenzamide ([11C]6g) with a molar activity of 267 GBq μmol-1 and 12% radiochemical yield in 21 min from the beginning of synthesis.